PENGARUH MATH ANXIETY DAN SELF EFFICACY TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA PADA MATERI SPLDV - Naura Syifa Salsabila; Siska Imelda; Virda Nurmalia; Rosida Rakhmawati Muhammad; Bambang Sri Anggoro; Dona Dinda Pratiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Problem solving is the process of finding a solution to a problem through the stages of: problem identification, cause analysis, development of alternative solutions, selection of the best solution, and implementation and evaluation of the results. This process requires critical and systematic thinking to achieve effective results. This study is intended to analyze the effect of math anxiety and self-efficacy on students' ability to solve mathematical problems on the material "system of linear equations of two variables (SPLDV)". This research utilizes a quantitative approach through quantitative methods. The sample in the study was composed of 50 VIII grade students who were determined through random sampling technique. Data were collected through questionnaires in measuring math anxiety and self-efficacy, as well as tests to see students' mathematical problem solving skills. Data analysis in this study used multiple linear regression. The findings of this study explain that math anxiety affects students' mathematical problem solving ability. Then, self-efficacy affects students' mathematical problem solving ability, and math anxiety and self-efficacy together affect students' mathematical problem solving ability. Pemecahan masalah adalah proses untuk mencari solusi dari suatu persoalan melalui tahapan: identifikasi masalah, analisis penyebab, pengembangan alternatif solusi, pemilihan solusi terbaik, dan implementasi serta evaluasi hasilnya. Proses ini membutuhkan pemikiran kritis dan sistematis untuk mencapai hasil yang efektif. Penelitian ini dimaksudkan dalam menganalisis pengaruh math anxiety dan self-efficacy terhadap kemampuan siswa dalam memecahkan masalah matematis pada materi “sistem persamaan linear dua variabel (SPLDV)”. Penelitian ini memanfaatkan pendekatan kuantitatif melalui metode kuantitatif. Sampel pada penelitian tersusun dari 50 siswa kelas VIII yang ditentukan melalui teknik random sampling. Data dikumpulkan melalui kuesioner dalam mengukur math anxiety dan self-efficacy, serta tes untuk melihat kemampuan pemecahan masalah matematis siswa. Analisis data dalam penelitian ini menggunakan regresi linier berganda. Temuan penelitian ini menjabarkan bahwa math anxiety berpengaruh terhadap kemampuan pemecahan masalah matematis siswa,. Lalu, self-efficacy berpengaruh terhadap kemampuan pemecahan masalah matematis siswa, serta math anxiety dan self efficacy secara bersama-sama berpengaruh terhadap kemampuan pemecahan masalah matematis siswa.